Two Chronic Myeloid Leukemia Patients Presenting with Isolated Thrombocytosis - DOGU, Mehmet Hilmi; SERIN, Istemi; SUYANI, Elif (International Journal of Innovative Research in Medical Science, 2020)
Chronic myeloid leukemia (CML) usually present with high leukocyte counts and splenomegaly and isolated thrombocytosis is not a common condition in CML. We present two CML patients presenting with isolated thrombocytosis. Case 1: A 44-year-old male patient having isolated thrombocytosis with no additional features, was investigated with the suspicion of essential thrombocythemia (ET). However, he was found to be positive for BCR/ABL. Afterwords, imatinib with the dosage of 400 mg/day was started and a major molecular response was obtained. Case 2: A 74-year-old woman was referred to our outpatient clinic because of thrombocytosis. Her physical examination was normal without splenomegaly. Further investigations were planned with the doubt of ET, but the patient’s BCR/ABL was positive. She was started imatinib and a major molecular response was obtained. In these cases, we explored the presence of BCR/ABL and found that they were positive. In conclusion, screening for BCR/ABL has a substantial significance in patients with isolated thrombocytosis and not exhibiting CML findings, to provide an effective therapeutic approach for these patients.